Fat necrosis and polymicrobial wound infection caused partly by Raoultella ornithinolytica after reduction mammoplasty. (4th June 2018) - Ayoade, Folusakin; Mada, Pradeep Kumar; Alam, Mohammad
Abstract : Raoultella ornithinolytica is a rare opportunistic aerobic gram-negative bacillus that naturally exists in soil, water and plants. The pathogen has been described in association with diabetic foot infections, biliary infections, bacteraemia and native and prosthetic joint infections. Fat necrosis and wound infection following breast reduction surgery or other plastic surgeries caused by this pathogen have not been previously described. We present a case of bilateral fat necrosis, wound infection and dehiscence in a 24-year-old woman with no significant past medical problems. She initially had an uneventful early postoperative course but 3 weeks after surgery noticed pain and discharge from both nipple/areola area of both breasts which later developed into full-thickness fat necrosis and complete destruction of the nipple areolar complex. R. ornithinolytica, Escherichia coli and Enterococcus faecalis were identified from wound exudate cultures. She was treated with surgical debridement and 2 weeks of appropriate antibiotics with a favourable outcome.